THE IMPORTANCE OF SOCIAL SUPPORT AGAINST EXTERNAL PREGNANCY; A CASE REPORT - Zalfa Dinah Khairunnisa; Farida Fitriana; Euvanggelia Dwilda; Endah Sulistyowati (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Social Support is one of the things that is very necessary in pregnancy because of its very broad impact on the welfare of pregnant women and the fetus they contain. Assistance carried out by midwives and doctors on an ongoing basis or Continuity of Care for pregnant women, childbirth, postpartum, neonates is very necessary to do. Continuity of care in midwifery is a service that is achieved when there is a continuous relationship between a woman and a midwife. There needs to be an understanding that in providing midwifery services in Continuity of Care (COC) ways, it is hoped that mothers will be able to undergo pregnancy, childbirth, postpartum, neonates. Case report:. The importance of the support of husbands, family, relatives and health workers can have a huge impact on the condition of mothers and babies, especially during pregnancy. The role of companion is very important, especially for pregnant women who have lost support system during pregnancy by providing assistance both physically and psychologically because it will have an impact on pregnancy outcomes. Conclusion: The assistance that has been carried out through continuous care has been maximized. Even though mothers cannot directly monitor mothers, assistance has also been sought through telemedicine. It is hoped that midwives can maintain or improve quality service quality with Continuity of Care (COC) midwifery care during pregnancy, childbirth, postpartum and BBL.